Penerapan Metode Operational Competitiveness Rating Analysis (OCRA) dalan Penentuan Kelayakan Penerima Bantuan Langsung Tunai - Mesran, M.Kom, Mesran; Boangmanalu, Mei Mariana; Rohayani, Hetty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Bantuan Langsung Tunai (BLT) is a financial assistance program provided by the government to people in need. The main purpose of the BLT program is to support the economy of underprivileged families. In the selection process of BLT recipients, there are several criteria that must be considered, such as the condition of the house, the completeness of the files, the number of dependents, income, and the size of the land owned. To ensure that the determination of BLT recipient eligibility is done objectively and accurately, a decision support system is needed. One method that can be used is Operational Competitiveness Rating Analysis (OCRA). Through this method, it is expected that more accurate results can be obtained in determining who is entitled to receive BLT. The results of the research using the OCRA method showed that Jimmi Nababan was the most deserving BLT recipient candidate with the first rank and a score of 1,297. Thus, this decision support system is expected to be an effective solution in determining BLT recipients who really need this assistance.